2020
DOI: 10.24016/2020.v6n2.107
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and state-trait anxiety in Lima's university adults

Abstract: Background: This study sought to determine the relationship between self-esteem and anxiety in emerging adults from private universities in Lima. Method: Cross-sectional and correlational in design, it was aimed at determining the degree or strength of association between self-esteem, state/trait anxiety in emerging adulthood, for this purpose, the Coopersmith Self-Esteem Inventory (Form C) and the Anxiety Questionnaire State-Trait (IDARE) were applied to 221 university students of both sexes, aged between 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
2
0
1
Order By: Relevance
“…[21] Moreover, studies collectively corroborated the pivotal role of self-esteem in understanding trait anxiety. [2,23,24] Our study's consistent pattern of a negative association between self-esteem and trait anxiety found resonance in these investigations, affirming the reliability and generalizability of self-esteem as a predictor of trait anxiety. In summary, this comprehensive examination provides empirical evidence supporting the fundamental role of TEI and self-esteem in predicting trait anxiety, offering valuable insights for theoretical advancement and practical applications in various domains, from education to workplace well-being.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…[21] Moreover, studies collectively corroborated the pivotal role of self-esteem in understanding trait anxiety. [2,23,24] Our study's consistent pattern of a negative association between self-esteem and trait anxiety found resonance in these investigations, affirming the reliability and generalizability of self-esteem as a predictor of trait anxiety. In summary, this comprehensive examination provides empirical evidence supporting the fundamental role of TEI and self-esteem in predicting trait anxiety, offering valuable insights for theoretical advancement and practical applications in various domains, from education to workplace well-being.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the gender imbalance of the study, with a predominantly female sample (69.4% female and 30.6% male), may affect the generalizability of the findings, especially considering the existing literature on gender differences in trait anxiety. [24] To summarize, this study revealed the significant relationship between Trait TEI, self-esteem, and trait anxiety. The findings reinforce existing knowledge by highlighting how high TEI and self-esteem are related to lower levels of trait anxiety.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Uno de los recursos más utilizados en el proceso de evaluación de la ansiedad-rasgo son los autoinformes. Así, son numerosos los estudios que han utilizado fundamentalmente el Cuestionario de Ansiedad Estado-Rasgo (STAI) o el Inventario de ansiedad rasgo-estado (IDARE) para medir la ansiedad en diferentes poblaciones: adolescentes (García-Rodríguez & García-Rodríguez, 2021;Méndez-Sánchez et al, 2021), estudiantes universitarios (Fernández-Martínez et al, 2021;Huerta-Ojeda et al, 2021;Pozos-Radillo et al, 2021;Santos-Pazos et al, 2021) y adultos (Bazán-Izquierdo, 2021;Casafranca, 2021;Rodrich-Zegarra, 2020). No obstante, dichos cuestionarios también han sido empleados para diferentes ámbitos, entre el que destacan estudios relacionados con la salud: depresión (Espinosa et al, 2020), parejas infértiles (Álvarez-Morales et al, 2019), sueño e ingesta alimentaria (Serrano et al, 2020), Burnout (Puig-Lagunes et al, 2021 o adicción a sustancias psicoactivas (Contreras-Olive et al, 2020).…”
Section: -300unclassified